EPOCHS. XI. The Structure and Morphology of Galaxies in the Epoch of Reionization to z ∼ 12.5 - Lewi Westcott; Christopher J. Conselice; Thomas Harvey; Duncan Austin; Nathan Adams; Fabricio Ferrari; Leonardo Ferreira; James Trussler; Qiong Li; Vadim Rusakov; Qiao Duan; Honor Harris; et al. (The Astrophysical Journal)
We present a structural analysis of 520 galaxy candidates at 6.5 < z < 12.5 with a signal-to-noise ratio of >10 σ in the F444W filter taken from the EPOCHS v1 sample, consisting of uniformly reduced deep JWST NIRCam data covering the CEERS, JADES GOODS-S, NGDEEP, SMACS-0723, GLASS, and PEARLS surveys. We use standard software to fit single Sérsic models to each galaxy in the rest-frame optical and extract their parametric structural parameters (Sérsic index, half-light radius, and axis ratio) and Morfometryka to measure their nonparametric concentration and asymmetry parameters. We find a wide range of sizes for these early galaxies, with galaxy sizes overall continuing to become progressively smaller in the high-redshift regime, following ${R}_{e}=\left(2.12± 0.28\right){\left(1+z\right)}^{-0.67± 0.06}$ kpc. We further find a galaxy size–mass correlation up to z ∼ 12, with galaxies of a given mass also becoming smaller. Using nonparametric methods, we find that galaxy merger fractions, classified through asymmetry parameters, at these redshifts remain consistent with those in the literature, maintaining a value of f _m ∼ 0.12 ± 0.07 showing little dependence with redshift when combined with the literature at z > 4. We find that galaxies that are smaller in size also appear rounder, with an excess of high axis ratio objects. Finally, we artificially redshift a subsample of our objects to determine how robust the observational trends we see are, determining that the observed trends are due to real evolutionary effects, rather than being a consequence of redshift effects.